FRI0493 Clinical Features of The Vogt-Koyanagi-Harada Syndrome. (15th July 2016) - Losanto, J.; Colman, N.; Duarte, M.
Abstract : Background: Vogt-Koyanagi-Harada's disease (VKHD) is a bilateral, diffuse and chronic granulomatous panuveitis characterized by serous retinal detachment. This disease is often associated with neurological, auditory and dermatological disorders. The incidence of appearance is low, affecting mainly young women between 30 years approximately. Objectives: The objective of the present study was to describe and to analyze the characteristics of patients with VKHD, followed in a third level hospital. Methods: Retrospective and descriptive study of patients with EVKH. A large number of clinical, epidemiological variables and treatment were recorded. Statistical analysis was performed with SPSS19.0 program. The qualitative variables were expressed as frequencies and percentages, quantitative variables in mean. Results: In the last 5 years, 3727 clinical records were reviewed and 8 patients were included. Of these, 5 (62.5%) were women with a mean age at diagnosis of 43 years old. All patients referred decreased visual acuity, 100% with bilateral panuveitis and 75% were associated with serous retinal detachment. Dermatological disorders was found in 25% (i.e. vitiligo, poliosis and alopecia), neurosensorial hearing loss in 25% and 12.5% of patients presented asthenia and fever. Neurological symptoms (ie epilepsy, meningismus, confusion, impaired balance) were found in 37.5%. About treatment, all patients received high doses of systemic glucocorticoids and 25% also received non-steroidal anti-inflammatory drugs (NSAIDs). 37.5% of patients received cyclophosphamide, 62.5% azathioprine and 12.5% methotrexate. Visual acuity improved in 75% of cases. Ocular complications were seen in 50% of patients, 12.5% with cataracts, 25% synechiae and glaucoma and band keratopathy in 12.5%. No patients required vitrectomy, nor developed ocular hypertension. Currently only 1 patient has active disease. Conclusions: In our series of VKHD patients, we found that all required immunosuppressive therapy due to the severity of the disease and with this aggressive treatment, the prognosis of this disease was favorable. Acknowledgement: Dra Gabriela Avila. Disclosure of Interest: None declared